The Political Economy of Food Aid in an Era of Agricultural Biotechnology - Jennifer Clapp (Global Governance, 2005)
Recent years have seen numerous rejections of food aid containing  genetically modified organisms (GMOs). The United States, as the principal donor of this aid, went on the defensive and blamed the European Union for hunger in developing countries. Rarely is food aid rejected. And rarely do food aid donors act so strongly to blame other donors. The reaction of both donors and recipients is also puzzling because it contradicts much of the literature from the 1990s that argued that the international food aid regime had become largely "depoliticized" following reforms to food aid policies in the 1980s. The current literature on food aid has not adequately addressed the ways in which the advent of GMOs has affected the food aid regime. I argue that scientific debates over the safety of GMOs, and economic factors tied to the market for genetically modified crops-both highly political issues-are extremely relevant to current debates on food aid